Moderating Effect of Financial Constraint on Relationship Between Accounting Conservatism and Investment Efficiency of Nigerian Consumer Goods Firms - Aminu Lawal; Shehu Usman Hassan (Journal of Accounting and Taxation, 2021)
This study explores the moderating effect of financial constraint on relationship between Accounting conservatism and investment efficiency of consumer goods firms listed on the Nigerian Stock Exchange market. The study used correlational and ex-post facto research design in a sample of 27 consumer goods firms. Secondary data for a period of 10 years (2010-2019) was used, and Advanced panel multiple regression was employed in data analysis. The results obtained from this research indicate that there is a significant relationship between accounting conservatism and investment efficiency. The study also found that there is a significant moderation effect between accounting conservatism and financial constraint on defining investment efficiency of consumer goods firms in Nigeria. The study concludes by showing that financial constraint has antagonistic role to accounting conservatism on explaining investment efficiency thus, conservatism may not improve investment efficiency in firms facing financial constraints. The study suggests that consideration of firms financial conditions should form an essential part of any analysis towards understanding the impact of Accounting conservatism more especially on investment behaviour, because of the influence financial constraint has on accounting conservatism is antagonistic in nature